The function rule that would help you find the values in the table is m = –3n.
To see why, let's take the first pair of values in the table: (n=2, m=-6). If we plug in n=2 into the function rule m = -3n, we get:
m = -3(2) = -6
which matches the value given in the table for m when n=2. We can do the same thing for the other pairs of values in the table and see that they all match up with the function rule m = -3n.
Which function rule would help you find the values in the table?
nm
2 –6 4 –12 6 –18
m = –3n m = n–6 m = n–3 m = –6n
(1 point)
1 answer